Efficiency of the para-divinylbenzene-sec-butyllithium reaction and di-anionic butadiene polymerization - Costa, Guido (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1977.